2008
DOI: 10.1175/2008jcli2380.1
|View full text |Cite
|
Sign up to set email alerts
|

The Continuum of Northern Hemisphere Teleconnection Patterns and a Description of the NAO Shift with the Use of Self-Organizing Maps

Abstract: In this study, the method of self-organizing maps (SOMs) is used with NCEP-NCAR reanalysis data to advance the continuum perspective of Northern Hemisphere teleconnection patterns and to shed light on the secular eastward shift of the North Atlantic Oscillation (NAO) that began in the late 1970s. A 20-pattern SOM analysis of daily, wintertime, Northern Hemisphere sea level pressure reveals a continuum of patterns that correspond closely with well-known teleconnection patterns. This analysis also reveals that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
190
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(204 citation statements)
references
References 26 publications
9
190
2
3
Order By: Relevance
“…The spatial shift of the NAO is considered to be closely related to the variability of the NAO index [13][14][15]20]. As shown in Table 2, there are positive correlations between the NAO index and the NAO spatial shift indices on the interdecadal time scale with a significant confidence level.…”
Section: Possible Mechanism For the Spatial Shift Of The Naomentioning
confidence: 99%
See 2 more Smart Citations
“…The spatial shift of the NAO is considered to be closely related to the variability of the NAO index [13][14][15]20]. As shown in Table 2, there are positive correlations between the NAO index and the NAO spatial shift indices on the interdecadal time scale with a significant confidence level.…”
Section: Possible Mechanism For the Spatial Shift Of The Naomentioning
confidence: 99%
“…Previous studies have suggested that the eastward shift of NAO in the late 1970s is probably due to increased greenhouse gas concentrations [12], a higher NAO index [13][14][15], increased North Atlantic storm activity [9,12], stronger mean westerly winds in the North Atlantic region [16,17] and the eastward shift of the Atlantic storm-track eddy [18,19], among which the higher NAO index is widely considered to be the most important because it is associated with increasing North Atlantic storm activity [9], stronger mean westerly winds in the North Atlantic region [16] and the eastward shift of the Atlantic storm-track eddy [18,19]. In addition to the zonal shift, Wu et al [20] found that the active centers of the NAO shift southward (northward) when the NAO index is in a negative-anomaly (positiveanomaly) phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the North Atlantic, the most prominent of the latter-at least during the winter-is the North Atlantic Oscillation (NAO). The NAO's spatial pattern consists of a pressure dipole with its two centers over the Azores and Iceland, respectively, while its changes over time manifest themselves primarily by low-frequency variability on the order of a season or years (Barnston and Livezey 1987;Hurrell 1995;Lau 1988a;Rogers 1997;Hilmer and Jung 2000;Jung et al 2003;Luo and Gong 2006;Johnson et al 2008;Feliks et al 2010Feliks et al , 2013. Luo et al (2012) recently summarized studies of NAO subannual variability.…”
Section: Introductionmentioning
confidence: 99%
“…The period from the late 70s exhibits also a change in the northern hemisphere teleconnection patterns (Johnson et al, 2008), which could be due to a warming trend in the tropical Sea Surface Temperatures (SST) (Hurrell et al, 2004). Werner et al (2000) identified the decade 1981-1990 as the onset of climate change in the North Atlantic European sector with a trend starting in the beginning of the 70s.…”
mentioning
confidence: 99%